Influences of Divorce and Children’s Child-Care (Nafqah) (Pengaruh Perceraian Dan Penjagaan Kanak-Kanak (Nafqah)) - Elshaigi, Suaad Bint Mohamed (Journal of Islam in Asia (E-ISSN 2289-8077), 2017)
Abstract Divorce is one of the disliked permissible acts. It is only recommendable when there are no other solutions left to remedy the demolishing marriage. For some divorce loving husbands, divorce is a means to take revenge, or to express anger, or to replace wives. These disliked acts in Islam make it worse, when the divorcing husbands run away from their responsibility to pay the child-care for his children his own flesh and blood. This paper looks into the psychological and behavioral effects of divorce on children, children’s child-care, its philosophy, its shariah rulings, its amount, and cases of its exemption. This gives the foundation to discuss reasons behind children’s deprivation of child-care and the resultant harms affecting both the children and the community. For solution, this research proposes obligatory salary deduction and imposing of punishment on the defaulting fathers, and formation of a special welfare fund to pay the child-care when the father defaults or delays the payment. Keywords: Divorce, disliked permissible act, children’s child-care, exemption of child-care, effects of divorce on children. Abstrak Perceraian adalah salah satu perbuatan halal yang tidak disukai. Ia hanya boleh dilakukan apabila tidak ada penyelesaian lain bagi perkahwinan yang semakin merosak. Bagi sesetengah orang, perceraian digunakan untuk membalas dendam, atau untuk menunjuk kemarahan atau untuk menggantikan isteri. Amalan ini yang tidak disukai Islam membuatnya kelihatan lebih buruk, apabila suami yang menceraikan melarikan diri dari tanggungjawab mereka untuk membayar penjagaan anak bagi darah dagingnya sendiri. Kajian ini melihat kepada kesan psikologi perceraian pada kanak-kanak, penjagaan kanak-kanak, falsafahnya, keputusan undang-undang, jumlahnya, dan kes pengecualiannya. Ini memberi asas untuk membincangkan sebab-sebab di sebalik kekurangan penjagaan bagi kanak-kanak dan bahaya yang menjejaskan kanak-kanak dan masyarakat. Untuk penyelesaian, penyelidikan ini mencadangkan potongan gaji wajib dan mengenakan hukuman terhadap ayah yang ingkar, dan mendirikan dana kebajikan khas untuk membayar penjagaan anak apabila bapanya ingkar atau menangguhkan pembayaran. Kata Kunci: Cerai, perbuatan halal yang tidak disukai, penjagaan kanak-kanak, pengecualian penjagaan kanak-kanak, kesan perceraian atas kanak-kanak